2007
DOI: 10.1177/0020872807081917
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence workfare program participants

Abstract: English We empirically analyzed a representative workfare program in South Korea, the Self-Sufficiency Program (SSP), using multinomial logistic regression. Our findings demonstrated that family income sources, program participation length and health status are important factors affecting the self-sufficiency of program participants. Based on these results, we recommend improvements in the current SSP. French Nous avons fait l’analyse empirique d’un programme de sécurité du revenu de Corée du Sud, le Self-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous research on farmworkers within the horticulture industry in the Western Cape found a similar income range, namely R112-R320 per week. 43 Of particular relevance here is the finding that more than half (51) of the 92 respondents who earned an income before WfW, had voluntarily substituted this employment for WfW. Even more noteworthy is the fact that, of those 51, the majority (31) used to be farmworkers.…”
Section: Previous Employmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous research on farmworkers within the horticulture industry in the Western Cape found a similar income range, namely R112-R320 per week. 43 Of particular relevance here is the finding that more than half (51) of the 92 respondents who earned an income before WfW, had voluntarily substituted this employment for WfW. Even more noteworthy is the fact that, of those 51, the majority (31) used to be farmworkers.…”
Section: Previous Employmentmentioning
confidence: 84%
“…It is often argued that traditional welfare grants tend to socially isolate recipients of such grants to a greater extent than PWPs do, as the latter enables beneficiaries to socially interact and build networks in a working environment. 8 Kim and Zurlo 43 also mention that PWPs are advocated on the grounds that they prevent the poor from becoming socially excluded.…”
Section: Sense Of Connection and Belonging To Teamsmentioning
confidence: 99%